1964
DOI: 10.1111/j.1365-2672.1964.tb04914.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inhibitors on Sulphate Reducing Bacteria: a Compilation

Abstract: Summary: The effects of about 200 bacteriostatic and bactericidal agents on sulphate reducing bacteria, including some hitherto unpublished results, are tabulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…It was observed that a pure culture of SRB can tolerate 0.3-0.8 mM of Cu (Booth and Mercer 1963), similar to what was observed by Saleh et al (1964), who also reported that SRB can tolerate around 1.5 mM of Zn. The use of 0.35 mM of Cd and 0.4 mM of Pb induced 50 % inhibition in a SRB pure culture (Loka Bharathi et al 1990), while Desulfovibrio desulfuricans was reported to be sensitive to concentrations of Ni and Zn above 0.17 and 0.20 mM, respectively (Poulson et al 1997).…”
Section: Effects Of Heavy Metals On Srbsupporting
confidence: 72%
“…It was observed that a pure culture of SRB can tolerate 0.3-0.8 mM of Cu (Booth and Mercer 1963), similar to what was observed by Saleh et al (1964), who also reported that SRB can tolerate around 1.5 mM of Zn. The use of 0.35 mM of Cd and 0.4 mM of Pb induced 50 % inhibition in a SRB pure culture (Loka Bharathi et al 1990), while Desulfovibrio desulfuricans was reported to be sensitive to concentrations of Ni and Zn above 0.17 and 0.20 mM, respectively (Poulson et al 1997).…”
Section: Effects Of Heavy Metals On Srbsupporting
confidence: 72%
“…Sodium chloride, 25 g./l., was added for salt-water organisms. Details of the preparation, sterilization and pH adjustment of this medium are given elsewhere (Saleh, Macpherson & Miller, 1964 (Postgate, 1953).…”
Section: Methodsmentioning
confidence: 99%
“…During winter the sulphate-reducing bacteria appear to tolerate a higher level of sulphide than in summer (Fig. 8); Saleh et al (1964) commented that temperature might modify the toxicity of sulphide. In late summer, when much of the sulphide has been released, the gradual decrease in temperature would result in an increase in the amount of sulphide which the sediment can hold, a decrease in sulphide toxicity, and consequently an increase also in bacterial numbers.…”
Section: Seasonal Variations In the Bacterial Community Of An Estuarimentioning
confidence: 99%